Opłata za korzystanie z programu komputerowego jako usługi - Żok, Krzysztof (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The purpose of the article is to present typical modes of determining the fee in Software as a Service and to refer these remarks to the regulation of remuneration in Copyright and Neighbouring Rights Act. The paper discusses the general assumption, that the author as a weaker party needs a protection, and considers the adequacy of the assumption in the context of computer programs, including Software as a Service. Subsequently there are described systems of payment for using the work and kinds of typical fees connected with the exploitation of an intangible good in the cloud. The fee depending on the size of the real use of the computer programs and the fee depending on the number of users were subjected to a scrutiny. On this basis the differences between Software as a Service and licensing computer programs delivered on data media are also indicated. In the conclusion it is stated, that the divergence in the mode of shaping the aforementioned fees results mainly from the technology applied to the exploitation of the work.